Type II Collagen Sponges Facilitate Tendon Stem/Progenitor Cells to Adopt More Chondrogenic Phenotypes and Promote the Regeneration of Fibrocartilage-Like Tissues in a Rabbit Partial Patellectomy Model - Wang, Wen; Qin, Shengnan; He, Peiliang; Mao, Wei; Chen, Liang; Hua, Xing; Zhang, Jinli; Xiong, Xifeng; Liu, Zhihe; Wang, Pengzhen; Meng, Qingqi; Dong, Fei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Objective Fibrocartilage transition zone (FC) is difficult to regenerate after surgical re-attachment of tendon to bone. Here, we investigated whether type II collagen-sponges (CII-sponges) facilitated tendon stem/progenitor cells (TSPCs) to adopt chondrogenic phenotypes and further observed if this material could increase the FC areas in bone-tendon junction (BTJ) injury model. Methods CII-sponges were made as we previously described. The appearance and pore structure of CII-sponges were photographed by camera and microscopies. The viability, proliferation, and differentiation of TSPCs were examined by LIVE/DEAD assay, alamarBlue, and PKH67 in vitro tracking. Subsequently, TSPCs were seeded in CII-sponges, Matrigel or monolayer, and induced under chondrogenic medium for 7 or 14 days before being harvested for qPCR or being transplanted into nude mice to examine the chondrogenesis of TSPCs. Lastly, partial patellectomy (PP) was applied to establish the BTJ injury model. CII-sponges were interposed between the patellar fragment and tendon, and histological examination was used to assess the FC regeneration at BTJ after surgery at 8 weeks. Results CII-sponges were like sponges with interconnected pores. TSPCs could adhere, proliferate, and differentiate in this CII-sponge up to 14 days at least. Both qPCR and immunostaining data showed that compared with TSPCs cultured in monolayer or Matrigel, cells in CII-sponges group adopted more chondrogenic phenotypes with an overall increase of chondrocyte-related genes and proteins. Furthermore, in PP injured model, much more new formed cartilage-like tissues could be observed in CII-sponges group, evidenced by a large amount of positive proteoglycan expression and typical oval or round chondrocytes in this area. Conclusion Our study showed that CII-sponges facilitated the TSPCs to differentiate toward chondrocytes and increased the area of FCs, which suggests that CII-sponges are meaningful for the reconstruction of FC at bone tendon junction. However, the link between the two phenomena requires further research and validation.